Electro encephalography screening of suspected epileptic patients in Erbil City - Hummad, Mutaz F. i (Zanco Journal of Medical Sciences (ZJMS), 2019)
Background and objective: Electroencephalography is an essential component in the evaluation of patients with epilepsy. Electroencephalography provides important information about background electroencephalography and epileptiform discharges and the interictal spike or sharp waves. This study aimed to differentiate between epileptic and non-epileptic patients through electroencephalography investigation and determine its relationship with certain socio-demographic and clinical characteristics. Methods: In this cross-sectional study included 400 cases (205 males and 195 females) with a mean age ± SD of 25 ± 14 years, referred to the private neurology clinic, Soran Medical Center between April 2013 and March 2017 for attacks of abnormal movements and or disturbed level of consciousness. Results: Age-related prevalence of epilepsy showed a significantly higher prevalence (P = 0.001) of the disease among those who were 20 years and more. Epileptic patients showed significantly (P = 0.001) higher sharp slow waves and sharp waves, which were mainly dominated by parietal and occipital regions of the brain. Electroencephalography finding showed higher Beta rhythm followed by Alpha and Delta rhythms (73.5%, 14.3% and 9.0%, respectively), Patients with epilepsy (generalized and focal) had shown best rhythm adoption in Beta rhythm (75.2% and 70.2%, respectively), followed by Alpha rhythm (13.2% and 14.8%, respectively). Focal to bilateral (secondary generalized) and generalized motor epilepsy were the most common diagnosis among the epileptic cases (45.4% and 43.4%, respectively). The overall sensitivity of electroencephalography was 67.8%, and specificity was 63.5%. Conclusion: The electroencephalography showed good sensitivity and specificity in diagnosing suspected epileptic patients, with interesting higher sensitivity than specificity. Not only the abnormal discharges, but the background dominating activity and the best rhythm adoption can help in the diagnosis of epilepsy.